Total value of the customer and targeted marketing strategies - Ryals , L. (Cranfield University, 2002)
The literature shows some recent calls for an end to 'unaccountable' marketing (Rust et al., 2001; Sheth and Sharma, 2001) and the use of customer lifetime value as an appropriate marketing metric (Rust et al., 2001). Some commentators recommend the application of shareholder value measures to the valuation of customer relationships (Uyemara, 1997; Mariotti, 1996). The thesis evaluates the application of shareholder value measures to the valuation of customers. Shareholder value involves both risk and return; therefore, the thesis argues, the risk of the customer or segment has to be identified before that customer's role in creating shareholder value for an organisation can be assessed. In addition, Relationship Marketing suggests that customer relationships have value in ways that are not easy to capture using traditional customer profitability analysis. The thesis explores different methods of valuing relationship benefits. As a result of the literature review, a model of the total value of the customer is developed which defines the Total Value of the Customer as the lifetime economic value of the customer (customer lifetime value adjusted for risk), plus the value of relationship benefits (Referral and Reference Effects, and Learning and Innovation). The model is operationalized using shareholder value measures and then tested in two collaborative research projects. The research finds that managers in the participating companies do not have good information about the lifetime value of their customer relationships. Evidence of changes in strategy as a result of a better understanding of the value of the customer is found. The research contributes to theory and knowledge through defining and calculating the Total Value of the Customer; demonstrating the application of shareholder value measures to the valuation of customers; finding and measuring relationship benefits measuring customer risk; and finding a link between the value of the customer and targeted marketing strategies.